Combined effect of bromelain and turmeric against acetic acid induced ulcerative colitis in wistar rats - reddi, Padmavathi; Keerthana, K. B; Lalitha Devi, A.; Sree Hari, Y.; Samad, Abdul (Creative Pharma Assent, 2021)
Objective: The present study planned to study the combined effect of Bromelain and Turmeric in acetic acid induced ulcerative colitis in Wistar rats. Methodology: Wistar rats of either sex (n = 30) were divided into 5 groups. Group – I, Sham control, administered single dose of vehicle rectally; Group –II, colitis control, colitis was induced by rectal administration of single dose of 2 ml of 3%, v/v of acetic acid in 0.9% saline; Group–III, treated with Turmeric (50 mg/kg/p.o); Group–IV, treated with Bromelain (100 mg/kg/p.o) and Group –V, treated with both Turmeric (50 mg/kg/p.o) and Bromelain (100 mg /kg/p.o). Colitis was induced in all the treatment groups on first day and drug treatment was continued for 7 days. During the treatment period, Disease Activity Index (DAI) was assessed daily and on 8th day White Blood Cell (WBC) Count and Differential Leucocyte Count (DLC) was performed and on 9th day all the rats were sacrificed for the assessment of intestinal inflammation, colon myeloperoxidase (MPO) levels and Histopathology. Results obtained were analysed by one-way analysis of variance followed by Tukey’s multiple comparison test. Results: Overall changes in DAI, Inflammatory scores, WBC, DLC and MPO has shown significant improvement with Turmeric and Bromelain compared to Colitis control. However, the combined therapy has shown to be more effective in alleviating ulcerative colitis compared to individual therapies. Conclusion: The present study recommends that the combination of Turmeric and Bromelain has synergistic effect in treating ulcerative colitis.